Water quality and phosphorus budget model for estimating the carrying capacity for fish rearing at Batang Ai reservoir, Lubok Antu, Sarawak - Leong, Chui Kit (Universiti Malaysia Sarawak, UNIMAS, 2012)
Fish cage culture in reservoir developed rapidly in order to meet the demand of fish for consumption. Phosphorus loading from fish cage culture activities could cause adverse impacts on the surrounding water bodies. Phosphorus budget model was used to estimate the maximum production from fish culture activities. The aims of this study were to determine the water quality and estimate the carrying capacity for fish rearing activities in Batang Ai reservoir, Sarawak. Carrying capacity of the reservoir was calculated based on Dillon and Rigler’s phosphorus budget model. Water quality parameters were measured at 5 stations, at subsurface, 10 m, and 20 m depths in October, November 2011 and April 2012 and at subsurface for station 6 in October, November 2011, and April 2012. Results show that chlorophyll a ranged from 0.38 to 6.02 mgm -3 , orthophosphate ranged from 0.01 to 0.27 mg/L, and total phosphorus from 0.03 to 0.24 mg/L. The higher concentration of orthophosphate and chlorophyll a at station 4 and 5 is due to sewage from longhouse community flushed by rain water in station 4 and effluent from fish culture in station 5. The carrying capacity was estimated at 5,948 and 10,641 tonnes per year based on the different phosphorus content in fish and feed. The estimated value was about 8 to 14 times higher than the current fish production at Batang Ai reservoir in 2011. Therefore, it is concluded that future expansion of cage culture activities in Batang Ai reservoir is still feasible.